Perbandingan Pengaruh Berbagai Jenis Model Pembelajaran Terhadap Keterampilan Proses Sains Mahasiswa Calon Guru Sekolah Dasar - Prima Mutia Sari; Sri Lestari Handayani; Nurwahyuni Nurwahyuni (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2020)
The aim of this research was to compare the influence of learning models on the science process skills of pre-service elementary school teacher. Research method was a quasi-experimental with The Matching Only Design.. The research population was all 5th semester students of pre-service elementary school teachers with a total population of 350 students. The sample was class 5E, 5G and 5H selected by Cluster Random Sampling.. The instrument was science process skills test. The data was analyzed using the Median test. The results showed that there was a significant difference in science process skills between Inquiry Learning, Problem Based Learning and Discovery Learning.